Program Kuliah Kerja Nyata Pembelajaran Dan Pemberdayaan Masyarakat Kkn-Ppm : Pentingnya Memahami Tentang Penyakit Tuberculosis Dan Hipertensi - Farecky, Adhe Firmansyah; Afriani, Sumita; Veronica, Bella; Tranado, Hengki (Jurnal Pengabdian Mitra Persada, 2024)
Activities of the Community Empowerment Learning-Real Work Lecture Program (KKN-PPM). Real Work Lecture Activities (KKN) are field activities for students taking the final part of the Bachelor's/D4/Applied Bachelor's education program. This program In fact, it is mandatory for all students, because the university believes that this program is able to encourage student empathy and can contribute to solving problems in society. Pagar Gading Village has an area of ​​120 Ha, located in Pino Raya District, South Bengkulu Regency, with 339 heads of families and a population of 1.546 people. The high incidence of Tuberculosis (TBC) & Hypertension and the lack of public knowledge about these diseases encourage Dehasen University students to provide health education to the community to provide a better understanding. Data collection uses primary data obtained from the results of questionnaires distributed to the community and secondary data obtained from the Pagar Gading Community Health Center. The method for evaluating the implementation of the Real Work Lecture Activities (KKN) program is to review the program's sustainability, effectiveness and sustainability of the program.targets of each work program.